2013
DOI: 10.1111/ene.12191
|View full text |Cite
|
Sign up to set email alerts
|

ANO5muscular dystrophy: clinical, pathological and molecular findings

Abstract: The results of the present study suggest that ANO5 mutations can be associated with amyloid deposition in muscle, but the nature of the amyloid deposits remains indeterminate, as does their relationship with cardiac involvement. ANO5 analysis should be considered in cases of muscle amyloid deposition of indeterminate etiology. Electrical myotonia can accompany ANO5-muscular dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 18 publications
8
73
0
4
Order By: Relevance
“…Spuler et al . and the authors of this study reported muscular dystrophies featuring isolated amyloid myopathy due to mutations in dysferlin (DYSF) and anoctamin‐5 (ANO5), respectively .…”
Section: Introductionmentioning
confidence: 88%
“…Spuler et al . and the authors of this study reported muscular dystrophies featuring isolated amyloid myopathy due to mutations in dysferlin (DYSF) and anoctamin‐5 (ANO5), respectively .…”
Section: Introductionmentioning
confidence: 88%
“…Interstitial or vascular amyloidosis of skeletal muscle (amyloid myopathy) without systemic amyloid deposition was first reported in dysferlinopathy (Fig. D and E), and subsequently in anoctaminopathy‐5 . Anoctaminopathy‐5 is the second most common cause of amyloid myopathy, exceeded in frequency only by immunoglobulin light‐chain amyloidosis .…”
Section: Lgmd Subgroupsmentioning
confidence: 95%
“…Unlike other LGMDs, asymmetric weakness is relatively common in these 2 muscular dystrophies, especially anoctaminopathy‐5, in which prominent asymmetrical atrophy of the quadriceps femoris and biceps brachii is the diagnostic hallmark . Patients with dysferlinopathy or anoctaminopathy‐5 may develop exercise intolerance or rhabdomyolysis preceding the fixed weakness . Myalgia and hyperCKemia without apparent weakness was a common presentation in a French cohort with anoctaminopathy‐5 .…”
Section: Lgmd Subgroupsmentioning
confidence: 96%
See 1 more Smart Citation
“…228,229 There are mixed reports of mild cardiac disease in patients with ANO5 mutations. Some have reported amyloid deposits in intramuscular vessels, similar to some cases of dysferlinopathy.…”
Section: Clinical Featuresmentioning
confidence: 99%